Data on ectoparasites infestation on small mammals from different habitats in east-coast Peninsular Malaysia - Nur Izzah Izzati, Ahmad; Noor Aisyah, A Rahim; Azuan, Roslan; Madinah, Adrus; Mariana, Ahamad; Marina, Hassan; Muhamad Safiih, Lola; Mohd Noor Afiq, Ramlee; Muhamad Aidil, Zahidin; Mohd Tajuddin, Abdullah (Elsevier, 2020)
This data article presents on the ectoparasites infestation on small mammals in Peninsular Malaysia. The dataset on ectoparasites infestation is important because it raises a major medical concern regarding the spread of potentially zoonotic disease from wildlife to human. Tick and chigger are the primary ectoparasites as reservoirs of vector-borne diseases found on small mammals in Malaysia. These small mammals that are infested with ectoparasites occupy various types of habitats, including human settlements, could be of community health risks as the carriers of potentially zoonotic diseases. Field samplings were conducted from February 2015 to February 2016 in three different ecological habitats of mixed dipterocarp forest, coastal forest and insular forest, in Terengganu, Malaysia. A total of 35 and 22 species of bats and rodents respectively were captured and examined for ectoparasites. Twenty-three species of bats and 16 species of small mammal were recorded as hosts for at least one species of ectoparasites. These findings show that the highest ectoparasite infestation occurred on bat community.